Physical Therapy Student Reports of Blood Pressure Guidelines Learned in the Classroom, and Observed and Practiced in Clinical Experiences. Issue 3 (July 2021) - Marks, Ted; Berg, Sarah Leah; Granek, Batsheva; Rybakov, Peter; Taranenko, Irina; Yee, Dana; Garcia, Ralph
Abstract : Purpose: The purposes of this study were (1) to investigate discrepancies between what physical therapy students report learning in the classroom regarding blood pressure (BP) guidelines and what physical therapy students report observing and practicing in clinical settings and (2) to establish whether students felt discomfort when discrepancies were encountered. Methods: This was a prospective descriptive survey study generated using a sample of convenience employing a survey developed by the researchers. Face and content validity were established through expert review. An email was sent to 21 New York State Physical Therapy Programs asking each program to share the survey with students in their programs who had completed clinical experiences. The responses were analyzed descriptively using frequency counts, percentages, and cross tabulations. Results: Responses were received from 206 students attending 13 different programs, or 61.9% of the programs contacted. More than half the students (53.4%) reported there were differences between what they learned during classroom instruction regarding BP assessment and what they saw and practiced in the clinic; 24.8% of students expressed discomfort related to discrepancies between what they learned in school and what they saw and practiced in the clinic. Inpatient and outpatient experiences were compared. Statistical differences were found indicating patients had their BP assessed less often in outpatient settings. In addition, students were less likely to discuss BP assessment with their clinical instructors (CIs) in outpatient settings and students were more likely to express increased competence taking BP after inpatient clinical experiences. Across all settings, 20.4% of students reported that neither they nor their CI ever measured BP during their most recent clinical experience. Conclusions: Across all settings, the BP assessment practices that students encounter in clinic differ from what students report learning is best practice during their physical therapy education. Students are more likely to encounter discrepancies in outpatient settings. For many students, encountering discrepancies gives rise to feelings of discomfort.